An investigation of fungal contamination on the surface of medicinal herbs in China. Issue 1 (December 2017) - Zheng, Run-sheng; Wang, Wen-li; Tan, Jing; Xu, Hui; Zhan, Ruo-ting; Chen, Wei-wen
Abstract Background The dried parts of medicinal herbs are susceptible to the infection of fungi during pre- or post-harvest procedure. This study aimed to investigate the presence of fungi and their metabolites mycotoxins on the surface of medicinal herbs collected from China. Methods Forty-five retail samples of 15 different medicinal herbs were collected from 3 different regions in China. Then the potential fungi were immediately washed off from the surface of each sample with 0.1% Tween-20 followed by incubation of the rinse on petri-dish with potato dextrose agar containing chloramphenicol at 28 °C. The obtained fungi were isolated as single colonies and then characterized by morphology and molecular identification using internal transcribed spacer (ITS) sequencing with extracted DNA. Meanwhile, the mycotoxin-producing potential of the isolates was studied by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results A total of 126 fungi were identified from the surface of samples by morphology and ITS sequencing, withAspergillus andPenicillium genera as the predominant contaminants. The mycotoxin-producing potential analysis showed that 6 of 8A. versicolor isolates could produce sterigmatocystin. All 3A. aculeatus isolates produced ochratoxin A, but only 1 of 3A. flavus strains produced aflatoxins B1 and B2 without G1 and G2 . Although the sample contamination ratios were high (≥95.6%), there was no significant difference (χ 2 = 1.05, P = 1.0) among the samples from 3 regions, which demonstrates the prevalent fungal contamination in the herbal medicines. Conclusion The prevalent contamination phenomenon of fungi and high potential risk of sterigmatocystin and ochratoxin A were observed in 45 medicinal herbs collected from China.